Modeling SDF-1-induced mobilization in leukemia cell lines - Zepeda-Moreno, Abraham; Saffrich, Rainer; Hoang, Thanh Van; Wuchter, Patrick; Ho, Anthony Dick (Experimental hematology, 2012)
The stromal cell-derived factor 1 (SDF-1) is essential for circulation, homing, and retention of hematopoietic stem cells in the bone marrow. Present evidence indicates that this factor might play an important role in leukemia cells as well. The aim of this study is to present a model of SDF-1-induced mobilization using leukemia cell lines. CXCR4 expression was compared in Kasumi-1, Jurkat, HL-60, KG-1a, and K562 cells by flow cytometry and Western blot. Migration was analyzed with Transwell assays, and adhesive cell-cell interaction was quantified with a standardized adhesion assay and flow cytometry. CXCR4 was expressed by all leukemic cell lines analyzed, although surface expression of this receptor was found in Kasumi-1 and Jurkat cells only. Correspondingly, SDF-1α effects on migration and cell-cell adhesion were observed in Kasumi-1 and Jurkat cells only, and this could be blocked by AMD3100 in a reversible manner. We have provided evidence that SDF-1α acts as a chemotactic and chemokinetic agent. In addition, surface expression of integrin-β2, activated leukocyte cell adhesion molecule and N-cadherin decreased after stimulation with SDF-1α. SDF-1α affects cell-cell adhesion and migration only in leukemia cells on which the CXCR4 receptor is present on the surface. An SDF-1 gradient is not necessarily required to induce migration, as chemokinesis can also occur. Upon stimulation with SDF-1, CXCR4 promotes modifications on the surface pattern of adhesion molecules, which have an influence on adhesion and migration.